Semi-aromatic polyimide dielectric film and preparation method thereof

By introducing pendant ethyl groups and multi-stage imidation treatment into the polyimide dielectric film, a high crosslink density and short-range ordered structure is formed, which solves the problem of insufficient heat resistance of polymer-based dielectric capacitors at high temperatures. Its high-temperature energy storage performance has been significantly improved.

CN119192636AActive Publication Date: 2024-12-27CENT SOUTH UNIV

Patent Information

Application Number
CN202411492601.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-27
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The insufficient heat resistance of polymer-based dielectric capacitors in high temperature environments limits their application in aerospace, hybrid vehicles and other industries. In particular, polyimide is prone to form charge transfer composites under high temperature and electric fields, which damages the Its electrical insulation properties.

Method used

By copolymerizing the aliphatic dianhydride monomer and the rigid diamine monomer containing pendant ethyl groups, a semi-aromatic polyimide dielectric film was obtained, and a specific imidation process was adopted, including multi-stage insulation and heating rate control. , form a short-range ordered structure and cross-link density, and improve the high-temperature energy storage performance of dielectric films.

Benefits of technology

The discharge energy density reached 7.48J/cm3 under the condition of an electric field intensity of 610MV/m at 200°C, and the energy efficiency exceeded 85%, and the discharge energy density reached 6.50J/cm3 at 90% energy efficiency, which significantly improved the dielectric High temperature energy storage performance of films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192636A_ABST
    Figure CN119192636A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric material preparation, in particular to a semi-aromatic polyimide dielectric film and a preparation method thereof. The preparation method of the semi-aromatic polyimide dielectric film comprises the following steps: mixing an aliphatic dianhydride monomer, a rigid diamine monomer containing a side ethyl group and a solvent, carrying out a copolymerization reaction to obtain a pre-polymer solution, forming a film from the pre-polymer solution, and carrying out an imidization reaction to obtain the semi-aromatic polyimide dielectric film, wherein the imidization reaction comprises a first heat preservation stage, a second heat preservation stage and a third heat preservation stage. The cross-linking density is improved by introducing an ethyl side chain into a semi-aromatic polyimide structure, meanwhile, a short-range ordered structure is controlled by adopting a specific imidization process, the structure of the obtained dielectric film is controlled from the molecular level, and the high-temperature energy storage performance of the dielectric film is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of dielectric material preparation, and in particular to a semi-aromatic polyimide dielectric film and a preparation method thereof. Background Art

[0002] Polymer-based dielectric capacitors are essential in industries such as aerospace, oil exploration, hybrid vehicles, and wind energy. However, the limited heat resistance of dielectric polymers greatly restricts their use in high-temperature environments, which poses a major obstacle to the development of polymer capacitors. The current commercial biaxially oriented polypropylene is generally used at temperatures not exceeding 80°C, and in order to be able to be used normally in hybrid electric vehicles, the solution is to maintain its excellent insulation properties through the joint operation of refrigeration equipment. In addition to biaxially oriented polypropylene, other commercial polymers such as polyphenylene ether, polyurethane, and polycarbonate also show good dielectric properties in certain applications, but their application in high-temperature environments is limited. Polyphenylene ether has excellent electrical insulation and heat resistance, but its heat deformation temperature is usually lower than that of polyimide, which limits its long-term stability at high temperatures. Although polyurethane has outstanding performance in flexibility and mechanical strength, its heat resistance and dielectric constant are not satisfactory at high temperatures, and it is prone to aging and performance degradation. In addition, polycarbonate has low heat resistance and a limited operating temperature range. Although it performs well in certain low-temperature applications, its high-temperature stability is insufficient. Therefore, these materials still face challenges in high-end applications. In contrast, polyimide is an ideal material for improving the performance of polymer capacitors for high-temperature applications due to its excellent thermal stability, chemical resistance and outstanding dielectric properties.

[0003] Polyimide (PI) has excellent thermal stability and is considered to be one of the most promising materials for the next generation of high-temperature, high-performance dielectric materials. Even so, PI still faces severe challenges: at high temperatures and electric fields, PI tends to form charge transfer complexes (CTCs), which will destroy its electrical insulation properties and limit its application under extreme conditions. This fundamental limitation calls into question the reliability and performance consistency of PI-based capacitors, especially in applications requiring stability under harsh conditions. Current methods to mitigate the formation of CTCs, such as molecular structure modification and the introduction of large bandgap inorganic fillers, have provided some directions. However, the high-temperature energy storage performance of dielectrics obtained by these methods is still unsatisfactory. Summary of the invention

[0004] The purpose of the present application is to provide a semi-aromatic polyimide dielectric film and a preparation method thereof in view of the defects and shortcomings of the prior art. The semi-aromatic polyimide dielectric obtained by the preparation method has excellent high-temperature energy storage performance.

[0005] In order to achieve the above object, the present application provides a method for preparing a semi-aromatic polyimide dielectric film, comprising the following steps:

[0006] The aliphatic dianhydride monomer, the rigid diamine monomer containing a side ethyl group and a solvent are mixed and copolymerized to obtain a prepolymer solution.

[0007] After the precursor solution is formed into a film, an imidization reaction is performed to obtain a semi-aromatic polyimide dielectric film, wherein the imidization reaction includes a first insulation stage, a second insulation stage and a third insulation stage, the first insulation stage is insulation at 65-75°C for 1.8-2.2 hours, the second insulation stage is insulation at 185-195°C for 1.8-4.2 hours, and the third insulation stage is insulation at 250-270°C for 0.8-1.2 hours.

[0008] Optionally, the aliphatic dianhydride monomer includes at least one of cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid 2,3:5,6-dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride and bicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride.

[0009] Optionally, the rigid diamine monomer containing a side ethyl group includes at least one of 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-methyl-6-ethylaniline) and 4,4'-diamino-3,3'-diethylbiphenylmethane.

[0010] Optionally, the molar ratio of the aliphatic dianhydride monomer to the rigid diamine monomer containing a pendant ethyl group is 1:0.9-1.1.

[0011] Optionally, the first insulation stage is at 70° C. for 2 hours, the second insulation stage is at 190° C. for 2 hours, and the third insulation stage is at 250-260° C. for 1 hour.

[0012] Optionally, the heating rate during the imidization reaction is 4-6°C / min.

[0013] Optionally, the thickness of the precursor solution liquid film obtained by the film forming is 275-325 μm.

[0014] Optionally, the copolymerization reaction is carried out at room temperature, and the copolymerization reaction time is 11-13 hours.

[0015] Optionally, after the imidization reaction, the preparation method further comprises a post-treatment, and the post-treatment comprises the following steps:

[0016] The film obtained by the imidization reaction is peeled off from the substrate.

[0017] On the other hand, the present application also provides a semi-aromatic polyimide dielectric film obtained by the preparation method described in the above technical solution.

[0018] The present application provides a method for preparing a semi-aromatic polyimide dielectric film, comprising the following steps: mixing an aliphatic dianhydride monomer, a rigid diamine monomer containing a side ethyl group and a solvent, performing a copolymerization reaction to obtain a prepolymer solution, forming the prepolymer solution into a film, and then performing an imidization reaction to obtain a semi-aromatic polyimide dielectric film, wherein the imidization reaction comprises a first insulation stage, a second insulation stage and a third insulation stage, wherein the first insulation stage is insulation at 65-75°C for 1.8-2.2h, the second insulation stage is insulation at 185-195°C for 1.8-4.2h, and the third insulation stage is insulation at 250-270°C for 0.8-1.2h. The present application increases the crosslinking density by introducing ethyl side chains into the semi-aromatic polyimide structure, and simultaneously adopts a specific imidization process to control the short-range ordered structure, and the specific temperature of the ethyl group and the imidization reaction is synergistically regulated to achieve moderate crosslinking, and the structure of the obtained dielectric film is controlled at the molecular level, which significantly improves the high-temperature energy storage performance of the dielectric film. It can be seen from the examples of the present application that the semi-aromatic polyimide dielectric obtained by the preparation method provided in the present application has a discharge energy density of up to 7.48 J / cm at 200°C and an electric field strength of 610 MV / m. 3 When the energy efficiency is above 85% and the energy efficiency of the semi-aromatic polyimide dielectric is 90%, the discharge energy density can reach 6.50 J / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and other objects, features and advantages of the present application will be apparent from the following description of preferred embodiments and accompanying drawings which illustrate the subject matter of the present application and its use, in which:

[0020] Figure 1 Schematic diagram of the synthesis of dielectric films prepared in Example 1 and Comparative Example 1.

[0021] Figure 2 This is a schematic diagram of the structure of the semi-aromatic polyimide dielectric film obtained in Example 1.

[0022] Figure 3 It is a diagram of the area fitting results of the short-range ordered structure and amorphous region of the dielectric films obtained in Example 1 and Comparative Examples 2-3.

[0023] Figure 4 The graph is a graph showing the chain spacing test results of the dielectric films obtained in Example 1 and Comparative Examples 1-5.

[0024] Figure 5 The DSC test results of the dielectric films obtained in Example 1 and Comparative Examples 1-5 are shown.

[0025] Figure 6 The thermogravimetric analysis results of the dielectric films obtained in Example 1 and Comparative Examples 1-5 are shown.

[0026] Figure 7 The infrared spectra of the dielectric films obtained in Example 1 and Comparative Examples 2-3 are shown.

[0027] Figure 8 The figures are the test results of dielectric properties of the dielectric films obtained in Example 1 and Comparative Example 1 at different temperatures.

[0028] Fig. 9 The figure is a test result of the energy storage performance of the dielectric films obtained in Example 1 and Comparative Examples 1-5 at a high temperature of 200°C.

[0029] Fig.10 This is a graph showing the pulse discharge performance test results of the dielectric film and biaxially oriented polypropylene film obtained in Example 1.

[0030] Fig.11 This is a graph showing the cyclic test results of the dielectric film obtained in Example 1 at 200° C. and 200 MV / m.

[0031] Fig.12 This is a diagram showing the energy storage performance test results of the dielectric film obtained in Example 2 at a high temperature of 200°C.

[0032] Fig.13 This is a diagram showing the energy storage performance test results of the dielectric film obtained in Example 3 at a high temperature of 200°C. DETAILED DESCRIPTION

[0033] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0034] The present invention provides a method for preparing a semi-aromatic polyimide dielectric film, comprising the following steps:

[0035] The aliphatic dianhydride monomer, the rigid diamine monomer containing a side ethyl group and a solvent are mixed and copolymerized to obtain a prepolymer solution.

[0036] After the precursor solution is formed into a film, an imidization reaction is performed to obtain a semi-aromatic polyimide dielectric film, wherein the imidization reaction includes a first insulation stage, a second insulation stage and a third insulation stage, the first insulation stage is insulation at 65-75°C for 1.8-2.2 hours, the second insulation stage is insulation at 185-195°C for 1.8-4.2 hours, and the third insulation stage is insulation at 250-270°C for 0.8-1.2 hours.

[0037] The present application firstly mixes aliphatic dianhydride monomers, rigid diamine monomers containing side ethyl groups and a solvent, and performs copolymerization reaction to obtain a prepolymer solution.

[0038] In some embodiments of the present application, the aliphatic dianhydride monomer includes at least one of cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid 2,3:5,6-dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride and bicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride. The dianhydride is preferably cyclobutanetetracarboxylic acid dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic acid dianhydride, 1,2,3,4-cyclopentanetetracarboxylic acid dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid 2,3:5,6-dianhydride, 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride or bicyclohexyl-3,4,3',4'-tetracarboxylic acid dianhydride, and more preferably bicyclohexyl-3,4,3',4'-tetracarboxylic acid dianhydride.

[0039] In some embodiments of the present application, the rigid diamine monomer containing a side ethyl group includes at least one of 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-methyl-6-ethylaniline) and 4,4'-diamino-3,3'-diethylbiphenylmethane, preferably 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-methyl-6-ethylaniline) or 4,4'-diamino-3,3'-diethylbiphenylmethane, and more preferably 4,4'-diamino-3,3'-diethylbiphenylmethane. In the present application, due to the introduction of the side ethyl group, the steric hindrance of the imidization ring-closing reaction of the polyimide is increased, thereby increasing the possibility of intermolecular imidization, and increasing the final crosslinking density of the semi-aromatic polyimide dielectric, thereby improving the high-temperature energy storage performance.

[0040] In some embodiments of the present application, the molar ratio of the aliphatic dianhydride monomer to the rigid diamine monomer containing a pendant ethyl group is 1:0.9-1.1, preferably 1:1.

[0041] The present application does not specifically limit the type of the solvent, as long as it can dissolve the aliphatic dianhydride monomer and the rigid diamine monomer containing the side ethyl group, and allow the two to copolymerize. In some embodiments of the present application, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, m-phenol and dimethyl sulfoxide, preferably N,N-dimethylacetamide, N,N-dimethylformamide, m-phenol or dimethyl sulfoxide, further preferably N,N-dimethylformamide, m-phenol or dimethyl sulfoxide, most preferably N-methylpyrrolidone or N,N-dimethylformamide. In some embodiments of the present application, the amount ratio of the aliphatic dianhydride monomer and the solvent is 1mmol:4-6mL, preferably 1mmol:5mL.

[0042] In some embodiments of the present application, the copolymerization reaction is carried out at room temperature, and the time of the copolymerization reaction is 11-13h, preferably 11.5-12.5h, and more preferably 12h. In some embodiments of the present application, the copolymerization reaction is carried out under stirring. The present application does not specifically limit the atmosphere of the copolymerization reaction, and the copolymerization reaction of the present application can be carried out in any atmosphere. In the examples of the present application, the copolymerization reaction is carried out in a nitrogen atmosphere. In the present application, if there is no special explanation, the room temperature refers to the ambient temperature, which is usually 15-35°C, preferably 15-30°C.

[0043] In some embodiments of the present application, the aliphatic dianhydride monomer, the rigid diamine monomer containing a side ethyl group and the solvent are mixed in the following manner: the rigid diamine monomer containing a side ethyl group is dissolved in a portion of the solvent, and then the aliphatic dianhydride monomer and the remaining solvent are added in sequence; the portion of the solvent is preferably half of the total amount of the solvent. In the polyimide reaction, dissolving the diamine first helps to ensure the uniformity of the reaction, so that the diamine and the dianhydride are fully in contact, thereby ensuring the smooth progress of the reaction. In addition, dissolving the diamine can better control the reaction rate, avoid overly fast reaction or the generation of by-products. For diamines with poor solubility, dissolving them first can improve the reaction efficiency, and at the same time can reduce the side reactions of the diamine with moisture or oxygen in the air.

[0044] In the present application, the aliphatic dianhydride monomer and the rigid diamine monomer containing a side ethyl group are copolymerized by copolymerization to obtain a prepolymer in the reaction solution. In the present application, after the copolymerization reaction is completed, the obtained reaction solution (i.e., the prepolymer solution) does not need to be treated and is directly used in the subsequent steps.

[0045] After obtaining the precursor solution, the present application forms a film of the precursor solution and then performs an imidization reaction to obtain a semi-aromatic polyimide dielectric film.

[0046] In some embodiments of the present application, before film formation, the method further includes degassing the precursor solution. The present application does not specifically limit the specific method of degassing, as long as it can remove the gas in the precursor solution. In some embodiments of the present application, the degassing method is vacuum degassing; those skilled in the art can determine the specific conditions of the vacuum degassing by conventional technical means; in some embodiments of the present application, the pressure of the vacuum degassing is 0.1 kg / cm 2 The vacuum degassing time is 2 minutes.

[0047] The present application does not specifically limit the thickness of the liquid film of the precursor solution obtained by film formation, and those skilled in the art can adjust it according to the thickness of the desired dielectric film. In some embodiments of the present application, the thickness of the liquid film of the precursor solution obtained by film formation is 275-325 μm, preferably 300 μm, and the thickness of the obtained semi-aromatic polyimide dielectric film is about 10 μm.

[0048] The present application does not specifically limit the film-forming method, as long as a liquid film of a desired thickness can be obtained. In the embodiment of the present application, after the precursor solution is poured on the substrate, a scraper is used to coat the substrate to form a film.

[0049] The present application has no special limitation on the material of the substrate. In the embodiment of the present application, the substrate is a glass substrate.

[0050] In the present application, the imidization reaction includes a first insulation stage, a second insulation stage and a third insulation stage, wherein the first insulation stage is 1.8-2.2 hours at 65-75°C, the second insulation stage is 1.8-4.2 hours at 185-195°C, and the third insulation stage is 0.8-1.2 hours at 250-270°C. In some embodiments of the present invention, the first insulation stage is 2 hours at 70°C, the second insulation stage is 2 hours at 190°C, and the third insulation stage is 1 hour at 250-260°C. In the imidization reaction process in the present application, in the first insulation stage, most of the solvent in the liquid film of the precursor solution can be removed; in the second insulation stage and the third insulation stage, imidization reaction and cross-linking reaction occur, and the solvent is removed at the same time to form a short-range ordered structure; the above-mentioned specific program heating process can ensure that the obtained semi-aromatic polyimide dielectric film has a high short-range ordered structure.

[0051] In the embodiment of the present application, the heating rate of the temperature rise during the imidization reaction is 4-6°C / min, preferably 5°C / min. In some embodiments of the present application, a slower heating rate is selected, which helps to orderly rearrange the molecular chains and reduce residual stress, thereby improving the thermal stability and mechanical properties of the material, while also ensuring that the imidization reaction is fully carried out, and improving insulation and chemical resistance. In addition, the above heating rate can promote the removal of by-products, avoid internal defects, and form a uniform and dense microstructure. However, a heating rate higher than the above may lead to problems such as stress accumulation, incomplete imidization, and structural defects, affecting the final quality of the material.

[0052] In some embodiments of the present application, the preparation method further comprises post-processing, and the post-processing comprises the following steps:

[0053] The film obtained by the imidization reaction is peeled off from the substrate.

[0054] The present application does not have any special restrictions on the peeling method, as long as the film can be completely peeled off. In an embodiment of the present application, the peeling method is to naturally cool the substrate with the film to room temperature and then immerse it in water for peeling, wherein the temperature of the water is preferably 80°C; after peeling by this method, the obtained film is preferably dried. The present application does not have any special restrictions on the drying method, as long as the moisture can be removed. In an embodiment of the present invention, the drying temperature is 100°C and the time is 24h.

[0055] On the other hand, the present application also provides a semi-aromatic polyimide dielectric film obtained by the preparation method described in the above technical solution.

[0056] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0057] Example 1

[0058] Under a nitrogen atmosphere, 0.1 mmol of 4,4'-diamino-3,3'-diethylbiphenylmethane and 0.5 mL of N-methylpyrrolidone were mixed, stirred and dissolved at room temperature of 25°C, and then 0.1 mmol of dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride and 0.5 mL of N-methylpyrrolidone were added in sequence to obtain a mixture, and the mixture was stirred and reacted at room temperature (15°C-30°C) for 12 hours to obtain a semi-aromatic polyamic acid (PAA) precursor polymer solution;

[0059] The semi-aromatic polyamic acid (PAA) precursor solution was heated to 0.1 kg / cm 2After degassing for 2 min (time) under vacuum pressure, pour it on a glass substrate and coat it with a 200 μm scraper, then place the glass substrate coated with the liquid film of the precursor solution in a blast oven, heat it to 70°C at a rate of 5°C / min and keep it for 2 h, then heat it to 190°C at a rate of 5°C / min and keep it for 2 h, then heat it to 260°C at a rate of 5°C / min and keep it for 1 h, then cool it naturally to room temperature, soak the substrate with the film in 80°C water to peel off the obtained semi-aromatic polyimide film, and then dry it at 100°C for 24 h to obtain a semi-aromatic polyimide dielectric film.

[0060] Example 2

[0061] A dielectric film was prepared according to the method of Example 1, except that 4,4'-diamino-3,3'-diethylbiphenylmethane was replaced by 4,4'-methylenebis(2,6-diethylaniline), and 260°C in the imidization reaction was replaced by 250°C.

[0062] Example 3

[0063] A dielectric film was prepared according to the method of Example 1, except that 4,4'-diamino-3,3'-diethylbiphenylmethane was replaced by 4,4'-methylenebis(2-methyl-6-ethylaniline), and 260°C in the imidization reaction was replaced by 250°C.

[0064] Comparative Example 1

[0065] A dielectric film was prepared according to the method of Example 1, except that 4,4'-diamino-3,3'-diethylbiphenylmethane was replaced by 4,4-diaminodiphenylmethane.

[0066] Comparative Example 2

[0067] A dielectric film was prepared according to the method of Example 1, except that the temperature at 260° C. in the imidization reaction was replaced by 230° C.

[0068] Comparative Example 3

[0069] A dielectric film was prepared according to the method of Example 1, except that the temperature at 260° C. in the imidization reaction was replaced by 290° C.

[0070] Comparative Example 4

[0071] A dielectric film was prepared according to the method of Example 2, except that the temperature of 260° C. in the imidization reaction was replaced by 230° C.

[0072] Comparative Example 5

[0073] A dielectric film was prepared according to the method of Example 2, except that the temperature at 260° C. in the imidization reaction was replaced by 290° C.

[0074] Figure 1 The following is a schematic diagram of the synthesis of the dielectric film prepared in Example 1 and Comparative Example 1. When R is ethyl, the schematic diagram corresponds to the reaction process of Example 1. When R is hydrogen, the schematic diagram corresponds to the reaction process of Comparative Example 1. Figure 1 It can be seen that at 190℃ in the second heat preservation stage, the precursor undergoes intramolecular imidization reaction, and at 260℃ in the third heat preservation stage, imidization ring-closing reaction occurs between the precursors simultaneously (i.e., the reaction at 190℃ Figure 1 260°C is not shown) and cross-linking reaction (such as Figure 1 The intermolecular imidization reaction shown at 260°C in FIG) forms a short-range ordered structure.

[0075] Figure 2 Schematic diagram of the structure of the semi-aromatic polyimide dielectric film obtained in Example 1. Figure 2 As shown, in the dielectric film structure, the aggregated structure includes an amorphous region and a short-range ordered structure (π-stacking and ch-stacking). In the amorphous region, there are donor and acceptor effects both between molecules and within molecules, that is, there are electron complex transfer products. The specific imidization reaction process of Example 1 can accurately control the ratio of amorphous regions and short-range ordered structures, and the presence of ethyl groups increases the steric hindrance of the polyimide imidization ring-closing reaction, thereby increasing the possibility of intermolecular imidization and significantly increasing the crosslinking density. The short-range ordered structure and the crosslinked structure effectively synergistically optimize the high-temperature capacitance performance of the dielectric film, the short-range ordered structure can reduce the electron complex transfer product, and the crosslinked structure can maintain the stability of the polymer chain at high temperature. The presence of the short-range ordered structure reduces the donor-acceptor effect between molecules and within molecules, and reduces the charge transfer of electrons between molecules and within molecules. The crosslinked structure limits the movement of the polymer chain at high temperatures through the generation of a crosslinked network, so that the polymer has better heat resistance.

[0076] The dielectric films obtained in Example 1 and Comparative Examples 2-3 were characterized by X-ray diffraction (XRD), and the short-range ordered structures (π-stacking and ch-stacking) and the area of ​​the amorphous region were fitted. The results are as follows: Figure 3 As shown. Figure 3It can be seen that with the increase of the temperature in the third insulation stage, the area ratio of ch-stacking and π-stacking gradually decreases, which means that the temperature of the third insulation stage of the imidization reaction will cause a significant change in the aggregation structure of the semi-aromatic polyimide. When the temperature of the third insulation stage of the imidization reaction is 290°C, the area ratio of the amorphous region increases to more than 85%, which means that the electron complex transfer product is significantly increased, which is not conducive to the improvement of high-temperature energy storage performance.

[0077] The chain spacing of the dielectric films obtained in Example 1 and Comparative Examples 1-5 was tested by XRD. The results are as follows: Figure 4 shown. Figure 4 It shows that with the increase of the temperature in the third insulation stage, the chain spacing gradually decreases, indicating that the interaction between chains gradually increases, and a cross-linking reaction may have occurred; in addition, the chain spacing of the polyimide containing side ethyl groups is smaller than that of the polyimide without side ethyl groups prepared at the same temperature in the third insulation stage, indicating that the presence of side ethyl groups increases the degree of cross-linking.

[0078] The glass transition temperature and specific heat capacity of the dielectric films obtained in Example 1 and Comparative Examples 1-5 were tested by differential scanning calorimetry (DSC). Figure 5 As shown, Comparative Examples 3 and 5 do not have a glass transition region and are therefore not shown. Figure 5 It can be seen that as the temperature of the third insulation stage increases, the glass transition temperature increases and the specific heat capacity decreases, indicating that the degree of crosslinking gradually increases. The polyimide containing side ethyl groups has a higher glass transition temperature than the polyimide without side ethyl groups prepared at the same temperature of the third insulation stage, that is, the degree of crosslinking is greater, indicating that the presence of ethyl groups can increase the degree of crosslinking. The glass transition temperature of Example 1 is increased by 37°C relative to that of Comparative Example 1, while the glass transition temperature of Comparative Example 2 is only increased by 15°C relative to that of Comparative Example 4. When the temperature of the third insulation stage reaches 290°C, there is no glass transition region for both the product of Comparative Example 3 (containing side ethyl groups) and the product of Comparative Example 5 (without side ethyl groups), which also means that the degree of crosslinking is further enhanced.

[0079] Thermogravimetric analysis (TGA) was performed on the dielectric films obtained in Example 1 and Comparative Examples 1-5. The results are as follows: Figure 6 As shown. As can be seen from the figure, as the temperature of the third insulation stage increases, the thermal decomposition temperature decreases, indicating that the structure has changed and a less stable intermolecular imine bond has been formed. At the same time, the downward trend of temperature also indicates that the degree of crosslinking has deepened. Moreover, as the temperature of the third insulation stage increases, the mass loss decreases, which indicates that a crosslinking reaction has occurred. In addition, the mass loss of the dielectric film obtained in Example 1 is smaller than that in Comparative Example 1, indicating that its crosslinking density is relatively larger.

[0080] The infrared (FI-IR) spectra of the dielectric films obtained in Example 1 and Comparative Examples 2-3 were tested. The results are as follows: Figure 7 As shown. At 1602cm -1 The peak at corresponds to the C=O stretching vibration peak of tertiary amide or secondary amide, which becomes gradually obvious with the change of temperature in the third insulation stage, indicating the existence of cross-linking reaction.

[0081] The dielectric properties of the dielectric films obtained in Example 1 and Comparative Example 1 were tested at different temperatures. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that from the frequency of 10 2 Hz to 10 6 Hz, the dielectric constant of the dielectric film obtained in Example 1 changes by 0.09, 0.13 and 0.22 at working temperatures of 150°C, 200°C and 250°C, respectively, and the dielectric loss changes by 0.04, 0.011 and 0.020 at working temperatures of 150°C, 200°C and 250°C, respectively. The dielectric constant of the dielectric film obtained in Comparative Example 1 changes by 0.11 at 150°C, 200°C and 250°C, and the dielectric loss changes by 0.011, 0.0040 and 0.015 at working temperatures of 150°C, 200°C and 250°C, respectively, indicating that both dielectric films have good dielectric stability and small changes, which is mainly due to the cross-linking reaction of the polymers, making both polymers have better heat resistance. At a frequency of 10 2 At a frequency of 10 Hz, the dielectric constants of the dielectric film obtained in Example 1 at 150°C, 200°C and 250°C are 3.52, 3.58 and 3.62 respectively, while the dielectric constants of the dielectric film obtained in Comparative Example 1 at 150°C, 200°C and 250°C are 3.34, 3.34 and 3.30 respectively; at a frequency of 10 6 At Hz, the dielectric constants of the dielectric film obtained in Example 1 at 150°C, 200°C and 250°C are 3.43, 3.45 and 3.40 respectively, while the dielectric constants of the dielectric film obtained in Comparative Example 1 at 150°C, 200°C and 250°C are 3.23, 3.23 and 3.19 respectively. It can be seen that at the same frequency and temperature, the dielectric constant of the dielectric film obtained in Example 1 is higher than that of Comparative Example 1, which is due to the fact that the cross-linking degree of the dielectric film obtained in Example 1 is better than that of the dielectric film obtained in Comparative Example 1.

[0082] The energy storage performance of the dielectric films obtained in Example 1 and Comparative Examples 1-5 at a high temperature of 200° C. was tested. The results are as follows: Fig. 9 The dielectric films obtained in Comparative Example 1 and Example 1 both have relatively high energy densities, which are 5.72 J / cm 3(electric field strength is 620MV / m, energy efficiency is 71.97%) and 7.48J / cm 3 (Electric field strength is 680 MV / m, energy efficiency is 87.18%). Due to the presence of ethyl, the energy efficiency of the dielectric film obtained in Example 1 can reach 90%, and the energy density is still relatively high, at 6.50 J / cm 3 This is because the presence of ethyl groups makes the cross-linking density higher when a certain proportion of ordered structures is maintained. This shows that the synergistic effect of short-range ordered structures and cross-linked structures is beneficial to the suppression of loss and heat resistance of energy storage applications. The differences in cross-linking density and microstructure lead to a huge gap in performance, proving that the method of this application can effectively improve the high-temperature energy storage performance of dielectric films.

[0083] The pulse discharge performance of the dielectric film obtained in Example 1 and the biaxially oriented polypropylene (BOPP) film (with the same thickness as in Example 1) were tested. The results are as follows: Fig.10 As shown. Fig.10 It can be seen that under the pulse discharge of 200 MV / m at 200°C, the power density of the dielectric film obtained in Example 1 is 0.46 MW / cm 3 , the discharge time is 1.44μs. Under the pulse discharge of 120℃ (the highest operating temperature of BOPP) and 200MV / m, the power density of BOPP film is 0.12MW / cm 3 , and the discharge time is 3.01 μs. It can be seen that the power density of the dielectric film obtained in Example 1 is nearly 4 times that of BOPP, and the discharge time is only half of that, which proves that the dielectric film obtained in Example 1 has excellent high-temperature energy storage performance.

[0084] The dielectric film obtained in Example 1 was subjected to cyclic pulse discharge at 200°C and 200 MV / m to test its cyclic performance. Fig.11 As shown. Fig.11 It can be seen that while maintaining an energy efficiency of 90%, the cycle number of the dielectric film can reach 100,000 times, indicating that it has excellent cycle stability.

[0085] The energy storage performance of the dielectric film obtained in Example 2-3 was tested at a high temperature of 200°C. The results are as follows: Figure 12-13 As shown. Fig.12 and 13 It can be seen that the dielectric films obtained in Examples 2-3 can maintain a breakdown electric field of 680 MV / m, and the energy density can reach 7.24 J / cm 3 and 7.01 J / cm 3 , indicating that the dielectric film obtained in Example 2-3 also has excellent high-temperature energy storage performance.

[0086] While preferred embodiments of the present application have been shown and described, it is contemplated that various modifications of the present application may be devised by those skilled in the art within the spirit and scope of the appended claims.

Claims

1. A method for preparing a semi-aromatic polyimide dielectric film, comprising the following steps: The aliphatic dianhydride monomer, the rigid diamine monomer containing a side ethyl group and a solvent are mixed and copolymerized to obtain a prepolymer solution. After the precursor solution is formed into a film, an imidization reaction is performed to obtain a semi-aromatic polyimide dielectric film, wherein the imidization reaction includes a first insulation stage, a second insulation stage and a third insulation stage, the first insulation stage is insulation at 65-75°C for 1.8-2.2 hours, the second insulation stage is insulation at 185-195°C for 1.8-4.2 hours, and the third insulation stage is insulation at 250-270°C for 0.8-1.2 hours.

2. The preparation method according to claim 1, characterized in that: The aliphatic dianhydride monomer includes at least one of cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid 2,3:5,6-dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride and bicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride.

3. The preparation method according to claim 1, characterized in that: The rigid diamine monomer containing a side ethyl group includes at least one of 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-methyl-6-ethylaniline) and 4,4'-diamino-3,3'-diethylbiphenylmethane.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the aliphatic dianhydride monomer to the rigid diamine monomer containing a side ethyl group is 1:0.9-1.

1.

5. The preparation method according to claim 1, characterized in that: The first heat preservation stage is heat preservation at 70°C for 2 hours, the second heat preservation stage is heat preservation at 190°C for 2 hours, and the third heat preservation stage is heat preservation at 250-260°C for 1 hour.

6. The preparation method according to claim 1 or 5, characterized in that: The heating rate during the imidization reaction is 4-6°C / min.

7. The preparation method according to claim 1, characterized in that: The thickness of the precursor solution liquid film obtained by the film formation is 275-325 μm.

8. The preparation method according to claim 1, characterized in that: The copolymerization reaction is carried out at room temperature, and the copolymerization reaction time is 11-13 hours.

9. The preparation method according to claim 1, characterized in that: After the imidization reaction, the preparation method further comprises a post-treatment, and the post-treatment comprises the following steps: The film obtained by the imidization reaction is peeled off from the substrate.

10. The semi-aromatic polyimide dielectric film obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition, liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element

    CN103502312A

  • Polyimide composite film and preparation method and application thereof

    CN111171567A

  • Polyimide molding powder containing isomeric mixed diamine monomer and preparation method thereof

    CN113045754A

  • Crosslinked polyetherimide dielectric film as well as preparation method and application thereof

    CN118290785A

  • Transparent polyimide film containing alicyclic structure as well as preparation method and application of transparent polyimide film

    CN118667160A

Cited By

  • Polyimide film as well as preparation method and application thereof

    CN119842073A

  • A polyimide film, a method for preparing the same, and an application thereof

    CN119842073B

  • Heat-resistant fluorine-free semi-alicyclic polyimide as well as preparation method and application thereof

    CN120795320A